(untitled) (Research, Society and Development, 2021)
Anophthalmia is mainly caused by two etiological groups, trauma and medical conditions. In addition, anophthalmia creates difficulties in social, professional, and family adaptation due to psychological, and functional disorders related to eye loss. Studies show a positive influence on the personal relationship of patients with anophthalmia after being rehabilitated with ocular prostheses. However, in order to achieve a good aesthetic result in prosthetic eye rehabilitation, it is essential that the size and positioning of the orbital skeleton are adequate. Facial trauma can also cause defects associated with bone loss, and in these cases, reconstructive techniques aim to restore the appropriate bone contour. The aim of this work is to report a case where reconstructive treatment was performed on a patient victim of a long-term traffic accident sequel, using an alloplastic implant in polymethylmethacrylate (PMMA) and bone repositioning, so that an ocular prosthesis could be made. At the end of the treatment, after reconstruction of the frontal-nasal region in PMMA and repositioning of the left zygoma, the aesthetic objectives were achieved and the patient improved his self-esteem and social life.